Cross-Laminated Timber: Perspectives from a Bibliometric Analysis (2006–2018) - Abejon-Elias, R (Taylor and Francis Ltd., 2022)
A bibliometric analysis of the Scopus database was performed to identify research trends related to cross-laminated timber (CLT) from 2006, when the earliest publication was found, to 2018. The analysis revealed a rapidly increasing number of annual publications, great contribution of conference papers to the total scientific production regarding this topic, a high degree of transdisciplinary collaboration, and a particularly remarkable contribution by Canada and Italy. The applied bibliometric network analysis was useful to determine the strategic diagram of topic clusters and their evolution through time. Number of cited papers and analysis of frequent keywords provided insight to identify the most relevant research topics: the seismic performance of CLT structures, and the mechanical properties of connections between different CLT substructures. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Cross-laminated timber; bibliometric analysis; research trends